Physical fitness changes among amateur soccer players - Silva, Rui (2021)
Study aim: To assess changes in physical fitness of amateur soccer players after a pre-season training period and baseline fitness dependencies. Material and methods: Twenty-one amateur soccer players were assessed during the pre-season. The following physical vari ables were assessed before and after a two-month pre-season training period: (i) cardiorespiratory fitness, (ii) strength and power, and (iii) change of direction (COD). Results: Significant decreases were found for countermovement jump (CMJ) (p < 0.001; d = 1.161), drop jump (DJ) (p = 0.014; d = 0.958), and horizontal jump (HJ) (p = 0.042; d = 0.640), while no significant changes were found for the overall variables from the beginning to the end of pre-season. Fit players revealed significant decreases for CMJ (p = 0.002; d = –2.495), DJ (p = 0.004; d = –1.760), HJ (p = 0.028; d = –1.005), COD deficit (p = 0.034; d = 1.013), and maximal aerobic speed (MAS) (p = 0.026; d = –4.053). No significant changes were found for unfit players. Conclusions: Amateur soccer coaches should consider assessing physical qualities at the beginning of pre-season and use the free-of-charge monitoring tools such as session-rate of perceived exertion (s-RPE) during the training process.